The Moderating Effect of Debriefing on Learning Outcomes of IVR-Based Instruction: An Experimental Research - Qinna Feng (MDPI AG, 2021)
With its ability to afford immersive and interactive learning experiences, virtual reality has been widely used to support experiential learning, of which the learning effectiveness is promoted by the instructional component of debriefing. The current literature on debriefing mainly focuses on the traditional learning contexts while little is known on its effectiveness in immersive virtual reality (IVR) learning environments. Based on the theories of experiential learning and debriefing, this study designed a debriefing strategy based on simulated learning experience and investigated its effectiveness on knowledge and behavioral learning in an IVR learning program, using a randomized controlled trial with 77 elementary students from Hubei province in China. The study results support the efficacy of IVR on improving knowledge acquisition and behavioral performance, and reveal a significant moderating effect of debriefing on the effectiveness of IVR learning environments. The study confirms the critical role of debriefing in IVR-based instruction and provides theoretical and practical implications for the design and implementation of effective IVR learning environments.